2017
DOI: 10.1136/bjophthalmol-2017-310723
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-146a in regulation of fibrosis in orbital fibroblasts from patients with Graves’ orbitopathy

Abstract: miR-146a plays a role as a negative regulator in the production of TGF-β-induced fibrotic markers. Thus, miR-146a may be involved in the regulation of fibrosis in orbital fibroblasts from patients with GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 34 publications
2
47
0
1
Order By: Relevance
“…The increase in HA production and collagen deposition has been indicated to increase the volume of orbital tissue in GO, thereby aggravating the symptoms of eyeball protrusion (26). The results of the current study are consistent with those of a previous study, which reported that miR-146a downregulated the expression of collagen I and was associated with TGF-β-mediated fibrosis (11). In addition, the effect of miR-146a on HA production was examined in the present study, and it was revealed that overexpression of miR-146a inhibited HA production, which suggests that upregulation of miR-146a may reduce GAG aggregation in patients with GO.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in HA production and collagen deposition has been indicated to increase the volume of orbital tissue in GO, thereby aggravating the symptoms of eyeball protrusion (26). The results of the current study are consistent with those of a previous study, which reported that miR-146a downregulated the expression of collagen I and was associated with TGF-β-mediated fibrosis (11). In addition, the effect of miR-146a on HA production was examined in the present study, and it was revealed that overexpression of miR-146a inhibited HA production, which suggests that upregulation of miR-146a may reduce GAG aggregation in patients with GO.…”
Section: Discussionsupporting
confidence: 92%
“…Owing to the potent hydrophilic nature of HA, its accumulation has been indicated to accelerate the expansion of orbital tissues (10). Collagen I is considered to be a marker of fibrosis (11). Fibrocytes, which express CD34 and C-X-C chemokine receptor type 4, have been reported to produce collagen I and infiltrate tissues in response to multiple chemokines, including C-X-C motif chemokine 12 (12), which may result in fibrosis in orbital tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently documented that miR-146a-5p participates in the biogenesis of fibrosis in a variety of tissues [36][37][38][39][40]. In the pathogenesis of nonalcoholic fibrosing steatohepatitis, it has been shown that miR-146a-5p was significantly down-regulated in activated hepatic stellate cells (HSCs) and overexpression of miR-146a-5p suppressed HSC activation, as well as extracellular matrix deposition [41].…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory roles of miR-146a-5p in various types of fibrosis have been recently documented [ 15 , 20 , 24 , 34 , 48 ]. During S. japonicum infection, it was shown that miR-146 is considerably up-regulated in liver macrophages, suppressing the IFN-γ-induced differentiation of macrophages to M1 cells through targeting STAT1 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%